The Rome Statute of the International Criminal Court : a commentary - Cassese, Antonio (O.U.P. OxfordGB, 2002)
Looks at international criminal law, appraising the contributions of international tribunals. Re-examines the case law developed by these courts and tribunals. Establishes to what extent the Rome Statute codifies this body of law or instead departs from it. Makes a critical assessment of the statute as a viable working tool for international criminal justice.